2019
DOI: 10.1080/13102818.2019.1571440
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin selectively influences the transcription of pluripotency and differentiation markers in human non-cancer cells

Abstract: Melatonin (MEL) may influence the efficiency of reprogramming both by somatic cell nuclear transfer and by direct induction of pluripotent stem cells (iPSC) through a yet unidentified mechanism. Transcription factors linked to cell reprogramming and cell signalling may be differentially expressed according to cell differentiation status. To address the effect of MEL on the expression of transcription factors linked to reprogramming, we used two distinct in vitro models of cellular plasticity: human foreskin fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In non-cancerous settings, melatonin has been demonstrated to enhance pluripotency and stem cell proliferation at 500 ng/L (2.15 nmol/L) by inducing the expression of stem cell markers including Oct4 [ 822 ]. At 10 nmol/L concentration in human non-cancer cells, melatonin selectively upregulated transcription of pluripotency and differentiation markers such as NANOG [ 823 ], completely contrary to findings in ovarian cancer stem cell experiments where melatonin inhibited the invasion and migration of cancer stem cells by inhibiting NANOG expression, albeit at exceptionally high concentrations between 3.4 and 6.3 mM [ 824 ]. It is tempting to hypothesize that at higher concentrations, melatonin can modulate inhospitable environment to attenuate PrP C stress responses, whereas lower levels stimulate and support the natural, physiological protective activities of prions.…”
Section: The Effects Of Melatonin On Lipid Phase Transition Lipid Com...mentioning
confidence: 99%
“…In non-cancerous settings, melatonin has been demonstrated to enhance pluripotency and stem cell proliferation at 500 ng/L (2.15 nmol/L) by inducing the expression of stem cell markers including Oct4 [ 822 ]. At 10 nmol/L concentration in human non-cancer cells, melatonin selectively upregulated transcription of pluripotency and differentiation markers such as NANOG [ 823 ], completely contrary to findings in ovarian cancer stem cell experiments where melatonin inhibited the invasion and migration of cancer stem cells by inhibiting NANOG expression, albeit at exceptionally high concentrations between 3.4 and 6.3 mM [ 824 ]. It is tempting to hypothesize that at higher concentrations, melatonin can modulate inhospitable environment to attenuate PrP C stress responses, whereas lower levels stimulate and support the natural, physiological protective activities of prions.…”
Section: The Effects Of Melatonin On Lipid Phase Transition Lipid Com...mentioning
confidence: 99%
“…Recent research from our laboratory demonstrated that melatonin treatment stimulates the expression of pERK1/2 in human foreskin fibroblasts [ 70 ]. The data suggest that the activation of MT1 melatonin receptor is probably related to phosphorylation of ERK1/2 at least in expanding fibroblasts, which subsequently may act to alter gene expression and regulate cell fate.…”
Section: Mt1 and Mt2 -Activated Signaling Pathways Are Involved In Physiological Processesmentioning
confidence: 99%